TEACHER’S PERCEPTION ON THE USE OF ENGLISH-INDONESIAN CODE SWITCHING IN TEACHING - Yaqub AR, Atiqah Fajriyani; Korompot, Chairil Anwar; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study aims to assess how teacher’s perception the utilization of English-Indonesian code-switching at SMP Unggulan Darussalam Barandasi. There 1 English teacher participated in this study. This study is a qualitative descriptive study that uses observation and interviews as data collection techniques. This study uses two theories, namely, linguistic theory and sociolinguistic theory. Based on the findings, the data shows that there are 3 stages in finding the effectiveness of language use during the learning process, namely: language use (context of use, type of code switching, purpose, strategy), effectiveness of using code switching (contextual appropriateness, skill level, learning evaluation) and students understanding (conceptual understanding, ability to identify and strategy) and there is a comparison of teachers. The teacher considers it an effective teaching strategy to bridge the gap in understanding, especially for beginner students. Teachers agree that the use of code-switching must be done in a balanced way so as not to reduce the quality of English exposure.